The constitutionality of the Extinction of Ownership Process - Bobadilla Chero , Josue Fernando Emanuel (2024)
This article aims to elucidate the controversial issues that arise from the entry into force of Legislative Decree No. 1373, in which merit the following question arises: Does the process of extinction of ownership contravene the Peruvian constitutional order? This problem will be developed by first identifying the genesis of this institution at the international level and then analyzing it in the Peruvian normative context, thus concluding that the process of extinction of ownership is opposed to the Peruvian constitutional framework in the extreme in that it is not contemplated as a form of extinction of property, consequently, it violates constitutional rights. The research obeys a descriptive-analytical design, based on the review of legal and normative literature, which evidenced the need to propose constitutional reforms to avoid the arbitrariness of the process of extinguishment of ownership.